Chromatin remodeling and nucleoskeleton synergistically control osteogenic differentiation in different matrix stiffnesses - Xinxin Xu; He Zhang; Yuzhou Li; Fengyi Liu; Zheng Jing; Mingxing Ren; Tao Chen; Yiru Fu; Yanqiu Wu; Ping Ji; Sheng Yang (Materials Today Bio, 2023)
Matrix stiffness plays an important role in determining cell differentiation. The expression of cell differentiation-associated genes can be regulated by chromatin remodeling-mediated DNA accessibility. However, the effect of matrix stiffness on DNA accessibility and its significance for cell differentiation have not been investigated. In this study, gelatin methacryloyl (GelMA) hydrogels with different degrees of substitution were used to simulate soft, medium, and stiff matrices, and it was found that a stiff matrix promoted osteogenic differentiation of MC3T3-E1 cells by activating the Wnt pathway. In the soft matrix, the acetylation level of histones in cells was decreased, and chromatin condensed into a closed conformation, affecting the activation of β-catenin target genes (Axin2, c-Myc). Histone deacetylase inhibitor (TSA) was used to decondense chromatin. However, there was no significant increase in the expression of β-catenin target genes and the osteogenic protein Runx2. Further studies revealed that β-catenin was restricted to the cytoplasm due to the downregulation of lamin A/C in the soft matrix. Overexpression of lamin A/C and concomitant treatment of cells with TSA successfully activated β-catenin/Wnt signaling in cells in the soft matrix. The results of this innovative study revealed that matrix stiffness regulates cell osteogenic differentiation through multiple pathways, which involve complex interactions between transcription factors, epigenetic modifications of histones, and the nucleoskeleton. This trio is critical for the future design of bionic extracellular matrix biomaterials.